1995
DOI: 10.1212/wnl.45.2.356
|View full text |Cite
|
Sign up to set email alerts
|

Selective neuroanatornic abnormalities in Down's syndrome and their cognitive correlates

Abstract: We examined the pattern of neuroanatomic abnormalities in adults with Down's syndrome (DS) and the cognitive correlates of these abnormalities. Specifically, we compared this pattern with what would be predicted by the hypotheses attributing DS pathology to either premature aging or Alzheimer's disease. We measured a number of brain regions on MRIs of 25 subjects: 13 persons with the DS phenotype and 12 age- and sex-matched healthy volunteers. Study participants had no history of cardiovascular disease, diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
175
4
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(215 citation statements)
references
References 5 publications
33
175
4
3
Order By: Relevance
“…The brains of DS patients have been reported to be normal at birth, but most postmortem studies on adults have reported low brain weight, a small cerebellum, small frontal and occipital lobes, and a narrow superior temporal gyrus (Becker et al, 1991). Volumetric neuroimaging studies have shown smaller cerebellar, brainstem, and frontal lobes; smaller hippocampus volumes; and enlarged ventricles (Raz et al, 1995), consistent with postmortem studies. Down syndrome is caused by a total or partial triplication of chromosome 21 (Poissonnier et al, 1976).…”
supporting
confidence: 74%
“…The brains of DS patients have been reported to be normal at birth, but most postmortem studies on adults have reported low brain weight, a small cerebellum, small frontal and occipital lobes, and a narrow superior temporal gyrus (Becker et al, 1991). Volumetric neuroimaging studies have shown smaller cerebellar, brainstem, and frontal lobes; smaller hippocampus volumes; and enlarged ventricles (Raz et al, 1995), consistent with postmortem studies. Down syndrome is caused by a total or partial triplication of chromosome 21 (Poissonnier et al, 1976).…”
supporting
confidence: 74%
“…The recent observation that the size of dendrites in some brain areas is reduced in DYRK1A haploinsufficient mice indicates that DYRK1A dose reduction could affect the length and the complexity of the dendrites (Fotaki et al, 2002). Moreover, brains of patients with Down syndrome present size reduction, increased astrocyte number, delayed myelination, and several abnormal neuronal differentiation processes (reviewed in Coyle et al, 1986;Becker et al, 1991;Raz et al, 1995). Thus, our finding that overexpression of DYRK1A potentiates the neurite outgrowth of PC12 cells stimulated with NGF supports the fact that DYRK1A may be involved in signaling mechanisms that regulate dendritic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the brain structures which has been a focus of research is the hippocampal formation. Magnetic resonance (MR)-based in vivo measurement of hippocampal volume is an accepted technique, which has been performed in the aged 1 and healthy subjects, 2 and has revealed a number of structural abnormalities in a variety of neurological and psychiatric disorders, such as temporal lobe epilepsy, 3 Huntington's disease, 4 Turner's syndrome, 5 Cushing's disease, 6 Down's syndrome, 7 Alzheimer's disease (AD), 8 mild cognitive impairment, 9 schizophrenia, 10 major depression (MD), 11 bipolar disorder, 12 post-traumatic stress disorder (PTSD), 13 borderline personality disorder, 14 chronic alcoholism, 15 obsessive-compulsive disorder, 16 and panic disorder. 17 The MR-derived hippocampal volumetric technique has demonstrated good validity and reproducibility, [18][19][20] and accuracy of the measurements has been shown by MRI volumetric measurement of phantoms with a known volume.…”
mentioning
confidence: 99%